Internationalizing the curricula through COIL in Japanese higher education: Towards inclusive, accessible, and pluralistic internationalization - Leyla Radjai; Christopher D. Hammond (University of Groningen Press, 2024)
Presented in this paper are findings from a research project exploring policies and pedagogies for collaborative online international learning (COIL) in the context of Japanese higher education. Our study comprised a qualitative investigation of a government-funded COIL project, in which 13 Japanese universities were awarded funding from 2018 to 2023 to establish and implement COIL programs with international partner universities primarily in the United States. Through our study we aimed to gain an understanding of the perceived opportunities and challenges of COIL as a policy idea for internationalization and as a pedagogy for internationalization of curricula (IoC) in the Japanese context. To achieve this aim, our research design entailed a comprehensive document analysis and 12 semi-structured interviews with educators involved with the funded COIL programs at eight different Japanese universities. Findings revealed that various actors both enabled and blocked COIL as a form of IoC, and that COIL itself served in many contexts as a mechanism that shaped IoC at institutional and personal levels more broadly, beyond the confines of the respective COIL programs. We argue that COIL offers a viable means to contribute to an inclusive and collaborative internationalized curriculum in Japanese universities, given adequate institutional support and faculty buy-in.